Investigating the relationship between bank performance and accounting standards: Evidence from M&As in European banking - Ali İhsan Akgün (Journal of Capital Markets Studies (JCMS), 2022)
Purpose - The study aims to identify whether international financial reporting standards (IFRS) or local generally accepted accounting principles (GAAP) reporting provides investors and senior management of acquirer banks with superior information on target banks under post-merger bank performance. Design/methodology/approach - The authors examine the claim that IFRS improves corporate transparency and increases financial reporting quality in European Bank merger and acquisitions (M&As). The authors compare the financial performance of merged banks where the target and acquirer banks employed the same reporting system (up to 305 merged banks) to the performance of a control group of banks not engaged in M&A activity (up to 1,690 European banks). Findings - Local GAAP reporting allows a more transparent assessment of financial performance using traditional indicators, making it a superior tool for assessing potential acquisition targets. Practical implications - Overall, the empirical findings are consistent with prior studies and indicate a significant relationship between local GAAP and post-merger performance, while IFRS does not contribute to post-merger bank performance. Originality/value - The study is one of the very few studies to investigate the relationship between bank performance, M&A activity and accounting standards in EU-28 countries. The primary contribution the finding of poor performance of IFRS reporting merged banks compared to local GAAP banks in EU-28 countries in line with prior results of Huian (2012). In addition, several deal- and bank-specific characteristics that affect accounting standards influence M&A transactions in European banks.
Keywords: 330; Bank performance; European banks; Financial reporting; IFRS; Local GAAP